Two-Dimensional MXenes: Innovative Materials for Efficient Thermal Management and Safety Solutions - XiaoYan Hu; Qi Fan; Shengchao Wang; Yanxin Chen; Degao Wang; Ke Chen; Fangfang Ge; Wenhu Zhou; Kun Liang (Research)
MXenes, a class of 2-dimensional transition metal carbides and nitrides, have garnered important attention due to their remarkable electrical and thermal conductivity, high photothermal conversion efficiency, and multifunctionality. This review explores the potential of MXene materials in various thermal applications, including thermal energy storage, heat dissipation in electronic devices, and the mitigation of electromagnetic interference in wearable technologies. Recent advancements in MXene composites, such as MXene/bacterial cellulose aerogel films and MXene/polymer composites, have demonstrated enhanced performance in phase change thermal storage and electromagnetic interference shielding, underscoring their versatility and effectiveness. Although notable progress has been made, challenges remain, including the need for a deeper understanding of photothermal conversion mechanisms, improvements in mechanical properties, exploration of diverse MXene types, and the development of sustainable synthesis methods. This paper discusses these aspects and outlines future research directions, emphasizing the growing importance of MXenes in addressing energy efficiency, health, and safety concerns in modern applications.